Investigation the effect of freeze–thaw cycle on fracture mode classification in concrete based on acoustic emission parameter analysis - Lian, Shuailong; Zheng, kun; Zhao, Yu; Bi, Jing; Wang, Chaolin; Huang, Yan sen (Construction & building materials, 2023)
•The variations of the mechanical properties is deeply investigated for concrete after freezing-thawing cycle action under different immersion condition.•The evolution of the deformation field on the concrete surface and the internal cracks are tracked in real-time by acoustic emission (AE) and digital image correlation (DIC) technology during the entire test process.•The micro-structure of the concrete specimens after F-T cycle treatment is microscopically observed with T2 distribution.•Acoustic emission parameter analysis method, Kernel density estimation (KDE) and K-means methods were introduced to classify different macroscopic crack types obtained from concrete specimens undergoing different F-T cycles under different immersion condition.•b-value analysis reveals the damage propagation of concrete specimens undergoing different F-T cycles under different immersion condition. This study experimentally investigates the influence of freeze–thaw (F-T) cycles on the mechanical properties and cracking features of concrete. The specimens, which are previously subjected to various numbers of freezing (-20 °C) and thawing (20 °C) cycles, are tested under unixial compression condition. Integrated acoustic emission (AE) and digital image correlation (DIC) techniques are adopted to study the mechanical characteristics of the concrete specimen subject to different F-T cycles under different immersion condition. The micro-structure of the concrete specimen after F-T cycle treatment is observed with T2 distribution by the nuclear magnetic resonance (NMR) technology. The changes in the amount of uniaxial compressive strength (UCS), elastic modulus, and peak strain of the specimens before and after various F-T cycles are comprehensively analyzed. The results show that the brittleness of the specimen decreases and the ductility increases as the number of F-T cycle increases. The peak load and elastic modulus decreased gradually with the increase of F-T cycle times, and the peak strain presented an upward trend. The concrete specimens without F-T cycle action or subjected to less F-T cycles action suddenly lose their bearing capacity and the failure mode is shear slipping. For the specimens undergoing more F-T cycles action, the stress–strain curve exhibits lower slopes during the strain softening stage. Kernel density estimation (KDE) results show that under the lower F-T cycle, the tensile crack has a higher AF (acoustic emission count/duration) value and a lower RA (rise time/amplitude) value, and the obvious shear/mixed cracking phenomenon occurs after the higher F-T treatment. The K-means clustering method has its advantages in the classification of AE cracking events. The b value increased with the increase of F-T cycles, indicating that F-T cycles can caused internal damage of the specimens, and the degree and scale of internal damage increased with the increase of F-T treatment times. Furthermore, the damage degree of the specimens under semi-immersion in water solution is greater than that under complete immersion in water solution.